2015
DOI: 10.11607/prd.2410
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Root Fragment Retention in Proximity to Dental Implants: A Series of Six Human Case Reports

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…11 For nine patients, implants were placed unintentionally in contact with residual root fragments. 10 12 13…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 For nine patients, implants were placed unintentionally in contact with residual root fragments. 10 12 13…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of a thick biofilm, calculus formation, and extensive bacterial infiltration on the implant surface were observed. 13…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, root retention with simultaneous implant placement is rarely feasible due to infection, fracture, or decay of the affected tooth or for strategic reasons. If compromised roots are maintained in close contact with an implant they may cause severe damage to the neighboring implants .…”
Section: Factors Influencing the Degree Of Dimensional Alterationsmentioning
confidence: 99%
“…Nevertheless, recent articles by Nevins et al 22 and Langer et al 23 reported belated implant failures when placed through impacted root remains. Scanning electron microscopic evaluation revealed that the failed implant surfaces were infiltrated by bacterial deposits and calculus.…”
Section: Discussionmentioning
confidence: 99%